PEMETAAN KEBISINGAN DAN SKRINING PENDENGARAN SEBAGAI UPAYA DETEKSI DINI GANGGUAN PENDENGARAN AKIBAT BISING DI SEKOLAH - Rinika Pranitasari, Ni Putu Oktaviani; Putra, I Dewa Gede Arta Eka; Pradiptha, I Putu Yupindra; Saputra, Komang Andi Dwi (Buletin Udayana Mengabdi; Vol 24 No 4 (2025): Buletin Udayana Mengabdi, 2024)
Noise consists of a blend of pure tone sounds that vary in fequency. Noise levels that exceed 85 dB can damage the inner ear and may lead to hearing loss. Common sources of  noise include occupational, leisure and academic environments. Noise-induced hearing loss is a permanent condition, so taking preventive measure is essential. To help reduce the risk of noise-induced hearing loss, community service activities are organized for the students of SMKN 1 Denpasar. Learning material about noise-induced hearing loss was presented to 158 students. An ear examination was performed on 48 machinary students, which showed that 1 student had unilateral CSOM and 8 students had earwax buildup. An audiometric screening identified 1 student with unilateral mild CHL and 47 students with normal hearing threshold (500 to 4k Hz). However, 5 of these students showed a decrease in hearing at the 6000 and 8000 Hz frequencies. Noise measurements with a sound level meter indicated that the activity in the practical room produced a sound intensity exceeding 97 dB. This social activity concluded with the distribution of 50 pieces of hearing protection. We hope this program can increase the awareness, promote early detection and prevent noise-induced hearing loss in school. Keywords : Academic noise, hearing screening, hearing loss, noise mapping, hearing protection